Effects of Hydrogen Peroxide and Sodium Hypochlorite Aging on Properties and Performance of Polyethersulfone Ultrafiltration Membrane - Li, Kai (Int J Environ Res Public Health, 2019)
Chemical reaction of main polymer and additive with oxidative cleaning agents plays an important role in aging of polymeric membrane for water and wastewater treatment. As a green and powerful oxidant, hydrogen peroxide (H(2)O(2)) can achieve good cleaning efficacy under alkaline condition, but its influence on membrane aging was poorly understood. In this study, degradation of polyethersulfone (PES) membrane due to H(2)O(2) exposure under alkaline condition (pH 9 and 11) was holistically investigated by humic acid (HA) filtration experiments and multiple membrane characterization techniques, with sodium hypochlorite (NaClO) aging examined as a comparison. Membrane permeability and HA retention rate was hardly changed by H(2)O(2) aging at an exposure dose of 500 g·h/L, whereas NaClO aging led to substantial increase of membrane permeability and significant decrease of retention ability. Meanwhile, H(2)O(2) aging slightly increased fouling propensity with HA filtration, while NaClO aging resulted in more serious fouling. ATR-FTIR and XPS analysis revealed much less degradation of PES and hydrophilic additive by H(2)O(2) than that by NaClO, and membrane morphology and surface properties were characterized to explain the variation of filtration performance. Overall, compared with cleaning with NaClO, membrane degradation can be minimized by cleaning with H(2)O(2).